Why New Issues and High-Accrual Firms Underperform: The Role of Analysts’ Credulity - Teoh, Siew Hong; Wong, T. J. (Review of Financial Studies, 2002)
We find that analysts’ forecast errors are predicted by past accounting accruals (adjustments to cash flows to obtain reported earnings) among both equity issuers and nonissuers. Analysts are more optimistic for the subsequent four years for issuers reporting higher issue-year accruals. The predictive power is greater for discretionary accruals than nondiscretionary accruals and is independent of the presence of an underwriting affiliation. Predicted forecast errors from accruals significantly explain the long-term underperformance of new issuers. The predictability of forecast errors among nonissuers suggests that analysts’ credulity about accruals management more generally contributes to market inefficiency.